ANALISA SENSITIVITAS SENSOR TGS PADA HIDUNG ELEKTRONIK UNTUK IDENTIFIKASI GANODERMA DI BAGIAN AKAR KELAPA SAWIT - Mhd Feri Desfri; Minarni Minarni; Dewi Laila Sari; Dewi Anjarwati Mahmudah; Ihsan Okta Harmailil; Irfan Cahyadi (Komunikasi Fisika Indonesia, 2022)
Palm oil is one of the main commodities for Indonesia. It is important to identify the disease-causing the decline in productivity. Root rot disease that causes total damage to oil palm plants due to fungal infection G. boninense sp has volatile organic compounds that can be detected using an electronic nose. The electronic nose system is designed with 6 sensor arrays, namely TGS 2612, TGS 822, TGS 2611, TGS 2610, TGS 813, and TGS 2620 which are sensitive to certain VOC compounds. The sample used was infected and uninfected oil palm seedlings aged 4 months. The detection process is carried out on plant roots. Python program is used as a data acquisition system in voltage retrieval. The obtained voltage is processed and further analyzed using a trapezoidal area to determine the sensor response in the identification of Ganoderma. The results of processing using a trapezoidal plane show that TGS 2611 has a very good response. The TGS 2611 sensor has a higher trapezoidal area in identifying oil palm plants that are attacked by Ganoderma with 4 classifications, namely healthy, moderate, sick, and severe.